MEDIASI STRUKTUR MODAL PADA PENGARUH LIKUIDITAS DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN LQ45 - Jemima Angella Setyana; Muhadjir Anwar (LPPM STIE Muhammadiah Bandung, 2026)
This research endeavors to examine the effect of liquidity and sales growth on firm value, with capital structure as a mediating variable, focusing on companies listed in the LQ45 Index of the IDX during the 2022–2024 period. The research is motivated by the decline in the Price to Book Value (PBV) of several LQ45 companies, indicating increasing investor skepticism and the need to reassess corporate financial strategies. This quantitative research employs a causal-associative design using secondary panel data from 30 companies consistently included in the LQ45 Index for three consecutive years, producing 90 firm-year observations. Liquidity is measured using the Current Ratio (CR), sales growth using the Sales Growth Rate, capital structure using the Debt to Asset Ratio (DAR), and firm value using the Price to Book Value (PBV). Data were analyzed through classical assumption tests, multiple regression analysis, and mediation testing using the Sobel Test with the aid of SPSS. The results show that liquidity and sales growth do not have a significant direct effect on firm value. Liquidity has a significantly negative effect on capital structure, while sales growth shows no significant effect. Capital structure positively and significantly influences firm value and mediates the relationship between liquidity and firm value. However, capital structure does not mediate the effect of sales growth on firm value. These findings conclude that firm value is more strongly influenced by an optimal capital structure rather than by liquidity or sales growth alone. Therefore, companies should avoid excessive idle cash and ensure that sales growth is accompanied by improved profitability to enhance firm value.